2016
DOI: 10.1074/jbc.m115.698365
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Regulate β-Cell Thioredoxin-interacting Protein (TXNIP) via Distinct Mechanisms and Pathways

Abstract: Thioredoxin-interacting protein (TXNIP) is a key regulator of diabetic ␤-cell apoptosis and dysfunction, and TXNIP inhibition prevents diabetes in mouse models of type 1 and type 2 diabetes. Although we have previously shown that TXNIP is strongly induced by glucose, any regulation by the proinflammatory cytokines tumor necrosis factor ␣ (TNF␣), interleukin-1␤ (IL-1␤), and interferon ␥ (IFN␥) has remained largely unexplored. Moreover, even though this three-cytokine mixture is widely used to mimic type 1 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…As a negative regulator of thioredoxin (TRX), TXNIP was found to be an inducer of the intracellular level of reactive oxygen species (ROS) (12). A number of studies have confirmed that TXNIP shows strong growth suppressive, metastasis inhibitory and proapoptotic functions (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…As a negative regulator of thioredoxin (TRX), TXNIP was found to be an inducer of the intracellular level of reactive oxygen species (ROS) (12). A number of studies have confirmed that TXNIP shows strong growth suppressive, metastasis inhibitory and proapoptotic functions (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Some identified miRNAs have functions in islet cells as well. In pancreatic cell lines, miR-17 downregulates thioredoxin-interacting protein, a pro-apoptotic regulator of beta-cells in diabetes 22 . In mouse islets, miR-7 (miR-7a) targets multiple components of the mTOR signaling pathway, and its inhibition promotes adult beta-cell replication 23 .…”
Section: Discussionmentioning
confidence: 99%
“…TXNIP was originally identified as a negative regulator of thioredoxin (Muoio, 2007), and subsequent studies found that TXNIP contributes to a wide array of processes in several tissues. Notably, TXNIP causes an increase in intracellular reactive oxygen species generation (Hong et al, 2016) that may inhibit hepatocellular carcinoma cell proliferation (Li et al, 2017a). TXNIP is key regulator of NLRP3 inflammasome activation, which plays an important role in liver fibrosis and hepatocellular carcinoma (Ringelhan et al, 2018;Wree et al, 2017), and its activation is associated with the NLRP3 inflammasome pathway in human diseases (Bai et al, 2019;Kim et al, 2019;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%